Macroscale connections of the mouse lateral preoptic area and anterior lateral hypothalamic area. Issue 13 (17th May 2022) - Hahn, Joel D.; Gao, Lei; Boesen, Tyler; Gou, Lin; Hintiryan, Houri; Dong, Hong‐Wei
Abstract: The macroscale neuronal connections of the lateral preoptic area (LPO) and the caudally adjacent lateral hypothalamic area anterior region (LHAa) were investigated in mice by anterograde and retrograde axonal tracing. Both hypothalamic regions are highly and diversely connected, with connections to >200 gray matter regions spanning the forebrain, midbrain, and rhombicbrain. Intrahypothalamic connections predominate, followed by connections with the cerebral cortex and cerebral nuclei. A similar overall pattern of LPO and LHAa connections contrasts with substantial differences between their input and output connections. Strongest connections include outputs to the lateral habenula, medial septal and diagonal band nuclei, and inputs from rostral and caudal lateral septal nuclei; however, numerous additional robust connections were also observed. The results are discussed in relation to a current model for the mammalian forebrain network that associates LPO and LHAa with a range of functional roles, including reward prediction, innate survival behaviors (including integrated somatomotor and physiological control), and affect. The present data suggest a broad and intricate role for LPO and LHAa in behavioral control, similar in that regard to previously investigated LHA regions, contributing to the finely tuned sensory‐motor integration that is necessary for behavioral guidance supporting survival and reproduction. Abstract : Prominent multilevel lateral preoptic area (LPO) and lateral hypothalamic area anterior region (LHAa) functional associations. Three nested tiers of functional grouping are represented (gray shaded tiles), and for each is listed functional grouping‐related gray matter regions with prominent connections to LPO and LHAa; outputs and inputs are indicated respectively by red and blue colored lines and arrows. Regions are color‐coded by tiles representing their major brain division (shown on the flatmap insert) and are listed in a topographic arrangement.